Corporate Responsibility in Unconsented Lending Practices: A Comparative Study of Indonesia, Singapore, and Australia - Anggriani, Devany; Fahira, Della Nur; Ismail, Muhammad Luthfi (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2025)
The practice of disbursing loans by fintech companies without the explicit consent of consumers raises serious legal issues, particularly concerning contract validity, consumer protection, and corporate criminal liability. In Indonesia, the existing legal framework does not clearly regulate corporate accountability in cases involving system errors or procedural deviations that harm consumers, unlike the stricter legal approaches implemented in Singapore and Australia. This study aims to analyze the forms of corporate liability in unauthorized lending practices and formulate an ideal legal accountability model for Indonesia through comparative analysis with the legal systems of Singapore and Australia. The research adopts a normative juridical method, using a statute approach, a comparative approach, and a conceptual approach. The analysis focuses on regulations such as POJK No. 10/POJK.05/2022, the Financial Services and Markets Act, and the ASIC Act 2001, as well as case studies including Ochroid Trading Ltd v Chua Siok Lui and ASIC v Rent 2 Own Cars. The findings show that Indonesia’s approach remains administrative and lacks a comprehensive foundation for criminal corporate liability, while Singapore and Australia have incorporated system flaws, transparency, and managerial involvement as key elements of legal responsibility. The study concludes that Indonesia needs to adopt a more progressive legal approach by reforming its regulatory norms and strengthening oversight of fintech operations. A liability model integrating corporate culture theory, vicarious liability, and identification theory is considered more effective in ensuring accountability and legal fairness within the digital financial sector.